2021
DOI: 10.1016/j.ajps.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the crucial roles of aliphatic tails in disulfide bond-linked docetaxel prodrug nanoassemblies

Abstract: Disulfide bond-bridging strategy has been extensively utilized to construct tumor specificity-responsive aliphatic prodrug nanoparticles (PNPs) for precise cancer therapy. Yet, there is no research shedding light on the impacts of the saturation and cis-trans configuration of aliphatic tails on the self-assembly capacity of disulfide bond-linked prodrugs and the in vivo delivery fate of PNPs. Herein, five disulfide bond-linked docetaxel-fatty acid prodrugs are designed and synthesized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The 3-dimensional structures of BNN6 and DiR with optimal combination formulation (3:1) were obtained using the Autodock Vina software. The runtime parameters and environment were consistent with the literature 47 . Moreover, the intermolecular interaction breakers (SDS, NaCl, and urea, 50 nM) were co-incubated with the B-BD NAs and T-BD NAs to determine the intermolecular forces.…”
Section: Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…The 3-dimensional structures of BNN6 and DiR with optimal combination formulation (3:1) were obtained using the Autodock Vina software. The runtime parameters and environment were consistent with the literature 47 . Moreover, the intermolecular interaction breakers (SDS, NaCl, and urea, 50 nM) were co-incubated with the B-BD NAs and T-BD NAs to determine the intermolecular forces.…”
Section: Methodssupporting
confidence: 59%
“…To screen the optimal synergistic dose radio of BNN6 and DiR, we first constructed the bared BNN6 and DiR co-assembly (B-BD NAs) using a nano-precipitation method 47 . In brief, 10 mg of BNN6 and 10 mg of DiR were dissolved in methanol (1 mL), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This provides a good foundation for developing a drug delivery systemDDS for cancer therapy. [ 34 , 35 , 36 ] Therefore, we first prepared a disulfide bond‐bridged PD1 nano‐cluster (S‐PD), in which the TEM showed a distinct spherical structure with a particle size of ≈150 nm (Figure S14 , Supporting Information). Then, the PD1 solution was co‐incubated with TDEVs with disulfide bond‐containing linkers in a homothermal shaker at 37 °C for 1 h to produce S‐PDNGs with cancer homing and reduction sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, we previously lucubrated the impact of disulfide bond bridge on paclitaxel (PTX)-oleic acid prodrug nanoassemblies and found that disulfide linkages could achieve effective reductive-selective drug release in response to excessive intracellular reductive glutathione (GSH) at tumor sites, greatly alleviating the side effects and improving antineoplastic efficacies [ 26 ]. Except for selective responsiveness, disulfide bonds also contribute to the self-assembly of prodrug-based nano-DDS by introducing molecular “structure defects” [ 27 , 28 ]. What is more, the distance between the disulfide bond and the ester bond is a pivotal point that has a great influence on drug release, cytotoxicity and antitumor efficacy in vivo [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%